Development and validity evaluation of Liquidambar formosana EST-SSR primers based on transcriptome sequencing - Hui LI; Yuanheng FENG; Shengsen TANG; Zhangqi YANG (Guangxi Zhiwu, 2023)
Liquidambar formosana is one of the important native tree species in Guangxi, which has high timber, ornamental and medicinal values. This study designs and develops EST-SSR markers of L. formosana based on data from the transcriptome sequencing. Primers were developed, and screened out by PCR amplification and polyacrylamide gel electrophoresis for high polymorphism, and the efficiency was tested by using 30 individuals from a wild L. formosana population to verify the practical application of these SSR primers. The results were as follows: (1) A total of 23 777 SSR loci were obtained by searching SSR Unigenes from transcriptome data. The repeat type of the SSR loci in L. formosana was dominated by mononucleotide repeat type (46.54%). The highest proportion of SSR loci (72.36%) was between 5 and 12 times. (2) A total of 262 pairs of SSR primers were developed, and among them, 139 pairs of effective amplifications with a success rate of 53.1%, and 18 pairs of them that could be used to steadily obtain clear bands were finally identified. (3) The polymorphism detection showed that all sites had a high degree of polymorphism. The number of alleles (Na), effective alleles (Ne), Shannon’s diversity index (I), observed heterozygosity (Ho) of the L. formosana population ranged in 2-4, 1.112 8-2.609 6, 0.208 9-1.112 7 and 0.275 9-1.000 0, the average values were 2.333 3, 1.957 4, 0.708 5 and 0.722 6, respectively. In conclusion, the dominant SSR repeat type and repeat motif in L. formosana are basically the same as those in other species, the developed 18 pairs of EST-SSR markers can meet the needs of population genetic studies of L. formosana, which provides abundant primers for the study of genetic diversity of L. formosana. It is of important significance to the protection, development and utilization of L. formosana.